Ask a New Question
Search
Balance the following redox equation
a) Use the standard reduction potentials table to balance the following redox equation:
H2O2 + I + H = H2O + I2 b) Balance the
6 answers
asked by
Laura
1,123 views
balance the redox equations:
IO3-(aq) -> I2(aq) and I-(aq) -> I2(aq) balance the redox equation: S2O3(-2) -> S4O2(2-) and I3- ->
1 answer
asked by
Jake
1,847 views
Balance the following redox reaction in acidic and basic solutions:
Fe(OH)2(s) + O2(g) --> Fe(OH)3(s) These are the steps my
0 answers
asked by
Emily
1,438 views
Balance the following redox equation by the oxidation number methode
Ag + HNO3 = AgNO3 + NO + H2O I have all the oxidation
2 answers
asked by
Amber
2,564 views
Balance the equation:
_MnO4– + _H+ + _Fe2+ => _Mn2+ + _H2O + _Fe3+ How do you do balance this redox reaction?
4 answers
asked by
Tom
592 views
Balance the following redox equation using the oxidation-number-change method. Describe each step you use to balance the
1 answer
asked by
girly girl
681 views
1) Balance this redox reaction using the oxidation-number method. Zn + O2 + HCl ® ZnCl2 + H2O
2) Balance this redox reaction
1 answer
asked by
Sara
910 views
Balance the equation in aqueous basic solution:
As2S3(s) + H2O2(aq) → AsO43-(aq) + SO42-(aq) I normally understand how to
2 answers
asked by
Joanne
5,045 views
I need help balancing this redox equation:
H2O2 + Ni+2 --> H2O + Ni+3 in basic solution. Here's what I have so far: Ni+2 --> Ni+3
2 answers
asked by
Chris
2,362 views
Balance the redox equation. It occurs in acid solution.
Sn(s) + H+(aq) = Sn2+(aq) + H2(g) I understand that first the equation
1 answer
asked by
Sha
2,321 views